Особливості морфогенезу серця в постнатальному періоді після внутрішньоплідної дії антигену та дексаметазону (анатомо-експериментальне дослідження) - Чернявський, Артур Валерійович; Чернявский, А. В.; Cherniavskyi, A. V. (Запорізький державний медичний університет, 2020)
Встановлено, що після внутрішньоплідного введення як стафілококового анатоксину, так і дексаметазону спостерігаються морфологічні зміни структур міокарда шлуночків серця щурів протягом 45 діб після народження, які проявляються змінами товщини стінок шлуночків, міжшлуночкової перегородки та артеріальних судин, а також змінами ядерно-цитоплазматичного відношення кардіоміоцитів та відносної площі, яку займають колагенові волокна і артеріальні судини в міокарді шлуночків серця щурів. Після внутрішньоплідного введення дексаметазону спостерігається передчасне зниження Ki-67+-кардіоміоцитів. Пренатальне введення стафілококового анатоксину приводить до збільшення вмісту PNA+-лімфоцитів в міокарді серця щурів. Установлено, что после внутриплодного введения как стафилококкового анатоксина, так и дексаметазона наблюдаются морфологические изменения структур миокарда желудочков сердца крыс в течение 45 суток после рождения, проявляющиеся изменениями толщины стенок желудочков, межжелудочковой перегородки и артериальных сосудов, а также изменениями ядерно-цитоплазматического отношения кардиомиоцитов и относительной площади, которую занимают коллагеновые волокна и артериальные сосуды в миокарде желудочков сердца крыс. После внутриплодного введения дексаметазона наблюдается преждевременное снижение Ki-67+-кардиомиоцитов. Пренатальное введение стафилококкового анатоксина приводит к увеличению содержания PNA+-лимфоцитов в миокарде сердца крыс. It was found that after intrauterine administration of both staphylococcal toxoid and Dexamethasone, morphological changes in the structures of the ventricles of the ventricles of the heart of rats are observed during the 45 days after birth. The decrease in heart weight in the group of animals after intrauterine administration of Dexamethasone is accompanied by a significant decrease of the relative area occupied by collagen fibers, arterial vessels, a decrease in the nuclear-cytoplasmic ratio. There are signs of premature stratification of myocardial layers and an increase of the ventricular wall thickness, interventricular septum, nuclear-cytoplasmic ratio, and premature reduction number of Ki-67+-cardiomyocytes. On the 14th day, a higher amount of heterochromatin was visualized in the nuclei of cardiac myocytes in the heart of rats after intrauterine administration of glucocorticoid, while in the control group cardiomyocytes nuclei contained more euchromatin. Thus, intrauterine administration of Dexamethasone leads to early maturation of cardiomyocytes, which reduces their number and may increase the risk of developing cardiovascular diseases in adulthood. After prenatal injection of staphylococcal toxoid was determined increase number of PNA+-lymphocytes in rat myocardium of the heart, accompanied by morphogenetic changes in myocardium - significantly thinner ventricular wall, interventricular septum, arteries wall, lower relative area, occupied by the connective tissue, arteries and smaller, in comparison with the control. In the experimental group after the intrauterine administration of staphylococcal toxoid, there is a decrease in number of mast cells in the external layer of myocardium at the 21st day of life. Changes in the nuclear-cytoplasmic ratio of cardiomyocytes in the ventricles of heart of antigen-treated animals are characterized by similar dynamics with control rats, but the value of nuclear-cytoplasmic ratio in the experimental group on the 9th and 14th day were significantly less than in the control group. Thus, intrauterine antigen impact disturbed intensity but not dynamics of cardiomyocytes proliferation.
Особенности морфогенеза сердца в постнатальном периоде после внутриплодного действия антигена и дексаметазона (анатомо-экспериментальное исследование)
Morphological features of heart in postnatal period after intrauterine effect of an antigen and Dexamethasone (anatomical and experimental research)
Keywords: серце; внутрішньоутробний період; антиген; дексаметазон; щур; морфогенез; сердце; внутриутробный период; крыса; heart; fetal period; antigen; Dexamethasone; rat; morphogenesis